Qath'y dan Zhanny Dalam Kewarisan Islam - Dena Kurniasari; Nabila Rahma Roihani; Shafriyana Mawarni Nurjannah (Media Syari'ah, 2021)
AbstractQath'i and zhanni in Usul fiqh are useful to explain the source text of Islāmic law, both the Qur'an and the hadith in two ways, namely al-tsubut (existence) or al-wurud (coming of the truth of the source) and al-dalalah (interpretation). In the context of qath'i and zhanny al-wurud the scholars agree that al-Qur'an and muthatith hadith are qath’y.. But they differ in terms of qath'i and zhanni from al-dalalah's side. The ulama of ushul fiqh states that there are religious texts that only contain one clear meaning and cannot debate other interpretations, also contain certain numbers, so the text is considered as a qath'i al-dalalah text. While contemporary scholars argue that the concept of qath'i and zhanni While contemporary scholars argue that the concept of qath'i and zhanni al-dalalah both the Qur'an and Hadith cannot be seen from the meaning of lafaz alone but also on the desired essence of the lafaz. Thus, the result is that religious texts in the field of inheritance law are open to modern interpretations. Islāmic inheritance include in the Zhanni al-dalalah group because relates to human relations and socio-economic roles, also, historically the verses on inheritance contain the essential meaning of justice.AbstrakQath’i dan zhanni dalam Ushul fiqh digunakan untuk menjelaskan teks sumber hukum Islam, baik itu al-Qur’an maupun hadits dalam dua hal, yaitu al-tsubut (eksistensi) atau al-wurud (kedatangan kebenaran sumber) dan al-dalalah (interpretasi). Dalam konteks qath’i dan zhanny al-wurud para ulama sepakat bahwa al-Qur’an dan hadits mutawatir adalah qath’i Namun mereka berbeda pendapat dalam hal qath’i dan zhanny dari sisi al-dalalah. Ulama ushul fiqh menyatakan bahwa jika suatu teks keagamaan hanya mengandung satu makna yang jelas dan tidak bisa membuka kemungkinan interpretasi lain, serta menyebutkan bilangan tertentu, maka teks tersebut dianggap sebagai teks yang qath’i dari sisi al-dalalah. Sementara ulama kontemporer berpendapat bahwa konsep qath’i dan zhanni al-dalalah baik al-Qur’an maupun Hadits tidak bisa dilihat dari kejelasan makna lafaz saja tetapi juga pada esensi yang diinginkan dari lafaz tersebut. Dengan demikian konsekuensinya adalah teks-teks keagamaan di bidang hukum waris terbuka terhadap penafsiran modern. Kewarisan islam masuk dalam kategori zhanny al-dalalah karena kaitannya dengan  hubungan antar manusia dan peran sosial ekonomi, selain itu jika dilihat secara historisnya ayat-ayat mengenai kewarisan mengandung makna yang esensi yaitu keadilan.